Evaluation of Blood Cultures From Patients Being Treated at an Infectious Diseases and Clinical Microbiology Clinic: A Three-Year Retrospective Analysis - Sagmak-Tartar, Ayse; Akbulut, Ayhan (Aves, 2018)
Objective: Bacteremia and sepsis are common causes of hospitalization. Their mortality rate is between 12%-80% and can be decreased with early diagnosis and treatment. In this study diagnosis for hospitalization, microorganisms isolated from blood cultures taken from patients in the Infectious Diseases and Clinical Microbiology Clinic and their susceptibility results were evaluated. Methods: The blood culture data of patients followed between January 2014-December 2017 at the Infectious Diseases and Clinical Microbiology Clinic of our hospital were retrospectively evaluated. Blood cultures were performed by Bactec (TM) 9120 (Becton Dickinson, Sparks, MD, USA) otomatized system. Contaminated blood cultures were excluded from the study. Only one isolate was included in the study when more than one isolate was grown from the same patient. Results: Microorganisms isolated from 124 blood culture bottles were clinically relevant. Of 124 patients 90 (72.6%) were male and 34 (27.4%) were female. The average age was calculated as 68.48 +/- 13.7 (minimum-maximum: 22-94). A total of 86 (69.2%) Gram-negative bacteria, 34 (27.3%) Gram-positive bacteria, and 4 (3.2%) fungi were detected among the microorganisms grown in blood cultures. The most frequently isolated microorganism was Escherichia coli, and Staphylococcus aureus was the second one. Colistin resistance was not determined in Gram-negatives. Except two Acinetobacter isolates, all microorganisms were found as imipenem-susceptible. Conclusions: Isolates of patients with bacteremia and their resistance profiles at the Infectious Diseases and Clinical Microbiology Clinic differ explicitly from those of infections acquired in the hospital. Since advanced age significantly increases the bacteremia risk, older patients should be evaluated carefully in terms of indications for hospitalization. Initial antibiotic therapy in patients with a suspicion of bacteremia should be broad-spectrum especially for the hospital-acquired infections in patients who have risk for bacteremia, and de-escalation should be applied if possible according to the blood culture results.
Bir infeksiyon hastalıkları ve klinik mikrobiyoloji kliniğinde tedavi edilen hastaların kan kültürü sonuçlarının değerlendirilmesi: üç yıllık bir retrospektif analiz
Keywords: Blood culture; bacteremia; infectious diseases